ダイ 26 ジ ナンキョク チイキ カンソク タイ ナツ タイ ホウコク 1984-1985 - 川口, 貞男; カワグチ, サダオ; Kawaguchi, Sadao (1986)
P(論文) 第26次観測隊は川口貞男隊長以下48名(うち福西 浩越冬隊長以下35名が越冬隊)で構成された。このほか防衛庁技術研究本部, 運輸省船舶技術研究所, 海上保安庁などから7名, 南極条約に基づく交換科学者として中国から2名が加わり, 夏隊と行動を共にした。1984年11月14日「しらせ」は東京港を出港し, 途中オーストラリアのフリマントル港に寄ったのち, 12月中旬昭和基地沖の氷縁に到着し, 16日昭和基地から第25次隊員2名を収容し, ブライド湾には19日に到着した。約80tの拠点建設などの荷物を輸送し, 12月31日には, あすか観測拠点を建設し, 8名の地学調査隊員などを残し, 1986年1月1日昭和基地に向かった。1月4日昭和基地に到着し, 直ちに輸送, 建設作業に着手した。1月16日輸送を完了し, 建設作業も順調に進み, 野外調査も計画どおり実施することができた。1月31日, 第25次隊と越冬を交代し, 2月4日昭和基地を離れ, 海洋および生物の船上観測を行い, 再びブライド湾に入り, 17日セールロンダーネ地学調査隊を収容した。その後海洋観測を実施しつつ3月2日氷隊を離れ北上し, ポートルイス, シンガポールを経て4月20日東京港に帰着した。 The summer operations of the 26th Japanese Antarctic Research Expedition (JARE-26) in 1984-1985 are reviewed. The icebreaker SHIRASE, carrying 48 expedition members led by the present author, 7 Japanese observers, 2 Chinese scientists and 760t of cargo, left Tokyo on 14 November 1984. After calling at Fremantle in Western Australia, the ship reached Breid Bay on 19 December, and the transportation of 80t of cargo and the construction of a new observation camp (Asuka Camp) were continued until 31 December. The ship was brought to Syowa Station on 4 January 1985,and the transportation of 680t of cargo by means of helicopters was completed by 16 January. After the accomplishment of field work in the Syowa Station area, SHIRASE was brought again to Breid Bay and the field party of the Sor Rondane Mountains was picked up by her. Then the ship left the Antarctic on 2 March and returned to Tokyo via Port Louis and Singapore on 20 April. As field activities, the geological, geomorphological and geodetic surveys were carried out in the Sor Rondane Mountains during about 40 days from January to February, and the geochemical studies of the lake water in the vicinity of Syowa Station were carried out. Scientific activities on shipboard were largely the continuation from previous years; oceanographic observations and ionospheric observation were carried out throughout the voyage, and biological researches were made in the ice area as part of the international "Biological Investigations of ...